PEMANFAATAN BUNGKIL BIJI KARET SEBAGAI EKSTENDER PEREKAT PADA KAYU LAPIS PULAI (Alstonia angustiloba Miq.) - M. I. Iskandar; Achmad Supriadi (JURNAL SAINS NATURAL, 2014)
Bungkil Use as Seed Rubber Extender Gluten in Plywood Pulai (Alstonia angustiloba miq.)        Indonesia has the largest area of rubber trees in the world, in 2012 reached 3.5 million ha. As a producer of latex, rubber plant also produces lumber and rubber seeds. Rubber seeds have a starch content of 15.9%, so have the opportunity to be made extenders as mixing the adhesive material. This study aimed to determine the utilization of rubber seed meal as an extender adhesives Urea Formaldehyde (UF) on plywood pulai. Extender material made with varying levels of 10%, 20% and 30% respectively of the weight of the liquid adhesive. Variations intended use extenders levels in order to know the quality of plywood produced from a wide variety of levels of these extenders. The results showed that the average moisture content of plywood island 7.97%, density of 0.485 g / cm3, and the bonding strength of 11.36 kg / cm2. The water content and the bonding strength of plywood pulai ware designed to meet the Indonesian National Standard. Statistically analysis levels extenders very significant effect on the bonding strength of plywood pulai. The higher levels of extenders, bonding strength of plywood pulai tends to decrease. Plywood pulai that has the best bonding strength value was the use of extender content of 10%.Keywords: extenders, adhesives, rubber seed meal, plywood, quality pulaiABSTRAK         Indonesia memiliki areal tanaman karet terluas di dunia, pada tahun 2012 mencapai 3,5 juta ha. Sebagai penghasil getah, tanaman karet juga menghasilkan kayu dan biji karet. Biji karet memiliki kandungan pati 15,9 %, sehingga berpeluang untuk dibuat ekstender sebagai bahan pencampur perekat. Penelitian ini bertujuan untuk mengetahui pemanfaatan bungkil biji karet sebagai ekstender perekat Urea Formaldehida (UF) pada kayu lapis pulai. Bahan ekstender dibuat dengan kadar bervariasi yaitu 10 %, 20 % dan 30 % masing-masing dari bobot perekat cair. Variasi penggunaan kadar ekstender bertujuan agar dapat diketahui mutu kayu lapis yang dihasilkan dari berbagai variasi kadar ekstender tersebut. Hasil penelitian menunjukkan bahwa rata-rata kadar air kayu lapis pulai 7,97 %, kerapatan 0,485 gr/cm3, dan keteguhan rekat 11,36 kg/cm2. Kadar air dan keteguhan rekat kayu lapis pulai yang dibuat memenuhi Standar Nasional Indonesia. Secara statistik kadar ekstender berpengaruh sangat nyata terhadap keteguhan rekat kayu lapis pulai. Makin tinggi kadar ekstender, keteguhan rekat kayu lapis pulai cenderung berkurang. Kayu lapis pulai yang memiliki nilai keteguhan rekat terbaik adalah yang menggunakan ekstender kadar 10 %.Kata kunci : Ekstender, perekat, bungkil biji karet, kayu lapis, kualitas pulai